The Princely Republic*. (16th June 2014) - Stacey, Peter
Abstract This article examines Seneca's theory of monarchy in De clementia. It focuses in particular on Seneca's appropriation and redefinition of some key terms within Roman political thought in order to present his theory as an account of the restitution of liberty to the res publica under the government of the virtuous princeps. By relocating the Roman body politic to a Stoic moral universe, Seneca is able to draw upon parts of his philosophical inheritance in order to substantiate his claim in some depth.